Integrated nutrient management effect on rice (Oryza sativa) - wheat (Triticum aestivum) system productivity in subhumid ecosystem - HEGDE, D M (The Indian Journal of Agricultural Sciences, 2013)
A long-term field experiment was initiated during 1983-84 at 8 locations (Ranjitsinghpura, Palampur, Pantnagar, Varanasi, Faizabad, Sabour, Jabalpur and Raipur) in rice (Oryza sativa L.) - wheat (Triticum aestivum L. emend Fiori & Paol.) cropping system. The results of the last 5-10 years indicated the possibility of substituting 50% N needs of rice through farmyard manure at Ranjitsinghpura, Palampur, Varanasi, Faizabad, Sabour and Raipur and through prickly sesban [Sesbania cannabina Pers. var cannabina Baker syn Sesbania aculeata (Retz.) Pers.] green-manure at Palampur and Raipur. In soils having high organic matter content at Pantnagar and high-clay soils at Jabalpur, N substitution by organic sources was not possible without any significant adverse effect on system productivity. Significant yield advantages with N substitution through farmyard manure at Palampur and prickly sesban green-manure at Raipur were also observed. Continuous rice-wheat cropping had variable effect on soil fertility depending on soil type, nutrient application and productivity levels. Integrated nutrient supply generally had beneficial effect on soil fertility.